Effectiveness of Citronella oil aromatherapy in enhancing appetite among stunted toddlers - Kasmirah; Zulliati; Kusvitasari, Hairiana; Yuliantie, Putri (Health Sciences International Journal, 2025)
Background: Stunting is a major public health concern, affecting millions of children worldwide, particularly in Indonesia, where 27.7% of children under five are affected. Poor appetite is a common issue among stunted children, contributing to malnutrition. Citronella oil, known for its appetite-stimulating properties, offers a potential intervention. Objective: To measure the effect of citronella oil aromatherapy on appetite in stunted toddlers. Method: A one-group pretest-posttest design was employed, involving 33 stunted toddler and parents at Long Kali Community Health Center. Appetite was assessed using the Child Eating Behavior Questionnaire (CEBQ) before and after exposure to citronella oil. Paired t-tests were used to analyze the data, with significance set at p < 0.05. Result: The results showed a significant improvement in appetite after the intervention, with the mean CEBQ score increasing from 23.76 to 60.45 (p < 0.001). Prior to the intervention, 81.8% of toddlers exhibited poor appetite, but post-intervention, 81.8% demonstrated good appetite. These findings suggest that Citronella oil aromatherapy is an effective method for stimulating appetite in stunted toddlers. The aroma activates the olfactory system, positively influencing the brain's limbic system, which regulates appetite and emotions. Conclusion: The statistically significant improvements highlight the potential for integrating Citronella oil into nutritional interventions for stunted children, particularly in resource-limited settings. This study contributes to the growing body of evidence supporting the use of aromatherapy as a complementary approach to addressing malnutrition and poor appetite in pediatric populations.